Does Instagram Influence the Matrealistic Lifestyle of Adult Instagram Users? Apakah Instagram Mempengaruhi Gaya Hidup Matrealistik pada Pengguna Instagram Usia Dewasa? - Arini, Diana Putri; Sri Indriani, Yuliana (Kanal: Jurnal Ilmu Komunikasi, 2024)
A materialistic lifestyle causes individuals to value material things as a goal in life or a form of personal well-being. Instagram social media facilitates a materialistic lifestyle, by showing one's existence through photos or short videos. This research aims to determine the role of Instagram user intensity and perceptions of influencers on the materialistic lifestyle of young adults. The research method used is quantitative with multiple regression analysis techniques. The search for respondents used the accidental sampling method by distributing a scale of intensity of use of Instagram, perceptions of influencers and materialistic lifestyles distributed via social media. There were 103 active Instagram users who were respondents to this research. The research results show that there is a very significant role of Instagram intensity and influencer perception with a value of 0.000 (p<0.05) and a contribution of 19.6% to the materialistic lifestyle. The results of the research imply that Instagram social media has an impact on individuals' views on materialistic values ​​as a life goal.